Design and Techno-economic Evaluation of Pokem (Setaria italica) Tresher Machine - istalaksana, Istalaksana; Payung, Paulus (Jurnal Teknologi Pertanian, 2013)
The threshing process  of pokem (papua wheat)  is still carried out with a traditional equipment with very limited  capacity. The aim of this study was to design the thresher, test the performance of the threser as well as carried out techno-economic evaluation of Pokem threshing machine. The results showed that the threser was successfully built with 6.54 kg/hr of threshing capacity, efficiency of threshing  of  94% and stem separation percentage of 78%. The techno-economic evaluation show the Net Present Value (NPV) of Rp. 18,796,600.00, BCR of  2.52, IRR of 64% and bigger commercial rate of interests (17%). The Payback Period (PBP) was 1.7 years. This results shows that the Threser machine has a potential to be developed in Papua.Keywords: Pokem, techno-economic evaluation, pokem thresher, design construct